Cognitive load theory as a framework for simulation-based, ultrasound-guided internal jugular catheterization training: Once is not enough. Issue 1 (8th November 2018) - McGraw, Robert; Chaplin, Tim; Rocca, Nicole; Rang, Louise; Jaeger, Melanie; Holden, Matthew; Keri, Zsuzsanna; Fichtinger, Gabor
Abstract : CLINICIAN'S CAPSULE : What is known about the topic? Cognitive load theory can be used to guide simulation-based training for procedural skills. What did this study ask? How can cognitive load theory be used to overcome the challenges of learning ultrasound-guided internal jugular catheterization? What did this study find? All trainees approached or exceeded expert benchmarks, with evidence of retention over time. Why does this study matter to clinicians? This curriculum may better prepare trainees for performing this important procedure in the clinical setting. ABSTRACT: Objective: The main objective of this study was to use the principles of cognitive load theory to design a curriculum that incorporates a progressive part practice approach to teaching ultrasound-guided (USG) internal jugular catheterization (IJC) to novices. A secondary objective was to compare the technical proficiency of residents trained using this curriculum with the technical proficiency of residents trained with the current local standard of a single simulation session. Methods: The experimental group included 16 residents who attended three 2-hour sessions of progressive part practice in a simulation lab. The control group included 46 residents who attended the current local standard of a single 2-hour simulation session just prior to their intensive care unit rotation. Technical proficiency was assessed using hand motion analysis and time to procedure completion. Results: After three sessions, median scores for right hand motion (RHM) (34.5; [27.0-49.0]), left hand motion (LHM) (35.5; [20.0-45.0]), and total time (TT) (117.0 s; [82.7-140.0]) in the experimental group were significantly better than the control group ( p <0.001). Results for eight experimental group residents who were assessed for retention at a later date revealed median scores for RHM (45.0; [32.0-58.0]), LHM (33.5; [20.0-63.0]), and TT (150.0 s; [103.0-399.6]), which were significantly better than those of the control group ( p =0.01, p <0.01, and p =0.02, respectively). Conclusion: These results support multiple sessions of progressive part practice in a simulation lab as an effective competency-based approach to teaching USG IJC in preparation for the clinical setting. Résumé: Objectifs: L'étude avait pour objectif principal d'appliquer les principes de la théorie des capacités cognitives dans l'élaboration d'un programme d'apprentissage visant à intégrer la méthode de la pratique progressive-fractionnée à l'enseignement du cathétérisme échoguidé de la jugulaire interne (JI) à des débutants. L'étude avait également pour objectif secondaire de comparer la compétence technique des résidents formés selon le nouveau programme avec celle des résidents formés selon la formule habituelle d'enseignement, appliquée à l'échelle locale, consistant en une seule séance de simulation. Méthode: Le groupe expérimental comptait 16 résidents, qui ont participé à 3 séances de pratique progressive-fractionnée, de 2 heures chacune, dans un laboratoire de simulation; le groupe témoin, quant à lui, comptait 46 résidents, qui ont participé à 1 seule séance de simulation, d'une durée de 2 heures, juste avant leur stage au service de soins intensifs, selon la méthode habituelle d'enseignement. L'habileté technique des participants a été évaluée à l'aide d'une analyse des mouvements de la main et du temps d'exécution de l'examen. Résultats: Après 3 séances de formation, les résultats médians relatifs aux mouvements de la main droite (MMD) (34, 5 [27, 0-49, 0]), à ceux de la main gauche (MMG) (35, 5 [20, 0-45, 0]) et au temps total d'exécution (TT) (117, 0 s [82, 7-140, 0]) dans le groupe expérimental étaient significativement meilleurs que ceux obtenus dans le groupe témoin ( p <0, 001). Par ailleurs, 8 résidents dans le groupe expérimental, soumis à une évaluation de la capacité de rappel des gestes à une date ultérieure, ont obtenu les résultats médians suivants: MMD (45, 0 [32, 0-58, 0]), MMG (33, 5 [20, 0-63, 0]) et TT d'exécution (150, 0 s [103, 0-399, 6]); ces chiffres sont nettement meilleurs que ceux enregistrés dans le groupe témoin ( p =0, 01, p <0, 01 et p =0, 02, respectivement). Conclusion: Les résultats obtenus confirment l'efficacité des séances fractionnées de pratique progressive, en laboratoire de simulation, comme méthode d'enseignement du cathétérisme échoguidé de la JI, axée sur les compétences, en vue de la préparation des étudiants au milieu clinique.